2014
DOI: 10.1093/carcin/bgu191
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine N-glucuronidation relative to N-oxidation and C-oxidation and UGT2B10 genotype in five ethnic/racial groups

Abstract: Nicotine metabolism influences smoking behavior and differences in metabolism probably contribute to ethnic variability in lung cancer risk. We report here on the proportion of nicotine metabolism by cytochrome P450 2A6-catalyzed C-oxidation, UDP-glucuronosyl transferase 2B10 (UGT2B10)-catalyzed N-glucuronidation and flavin monooxygenase 3-catalyzed N-oxidation in five ethnic/racial groups and the role of UGT2B10 genotype on the metabolic patterns observed. Nicotine and its metabolites were quantified in urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
242
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(265 citation statements)
references
References 43 publications
20
242
1
Order By: Relevance
“…It was previously reported that rabbits may be a particularly useful species for nonclinical studies of drugs that undergo N-glucuronidation in humans (Chiu and Huskey, 1998). However, N-glucuronidation by UGT2B10 on the pyridine moiety of desloratadine cannot be ruled out and has been shown to occur in the case of nicotine and cotinine glucuronidation (Murphy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that rabbits may be a particularly useful species for nonclinical studies of drugs that undergo N-glucuronidation in humans (Chiu and Huskey, 1998). However, N-glucuronidation by UGT2B10 on the pyridine moiety of desloratadine cannot be ruled out and has been shown to occur in the case of nicotine and cotinine glucuronidation (Murphy et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The limit of quantitation for these analyses was 0.4 ng/ml, and the coefficient of variation 6%. 40 Finally, daily data collection at home (EPDS, vaginal bleeding and breastfeeding) was done using EDC.…”
Section: Methodsmentioning
confidence: 99%
“…The relationship of the UGT2B10 rs2942857 alleles, mRNA expression, and RO5263397 and amitriptyline clearance in a panel of hepatocytes from individual African donors revealed that subjects carrying the homozygous genotype CC had poor metabolism and undetectable mRNA. Interestingly, a study on nicotine metabolism in different ethnic groups that was published shortly before our work was submitted for publication (Murphy et al, 2014) has identified the same polymorphic variant of UGT2B10 in African Americans. In other words, two independent studies, ours on a new drug candidate and theirs on nicotine metabolism, although initiated from very different starting points, reached the same finding and they can thus be viewed as supporting and validating each other.…”
Section: Ugt2b10 Splice Variant Increases Drug Exposure In Africansmentioning
confidence: 97%
“…Similar effects due to SNPs at splice sites resulting in undetectable mRNA species have been observed in other genes, such as TDP-43 (Avendaño-Vázque et al, 2012). In addition, while this article was in preparation, a new study was published, reporting that the same splicing mutation affects nicotine glucuronidation in African Americans (Murphy et al, 2014).…”
Section: Ugt2b10 Splice Variant Increases Drug Exposure In Africansmentioning
confidence: 99%